Fluorescent probes for imaging bioactive species in subcellular organelles. Issue 91 (27th October 2021) - Pramanik, Sumit Kumar; Das, Amitva
Abstract : Luminescent molecular probes and nanoscale materials have become important tools in biosensing and bioimaging applications because of their high sensitivity, fast response, specificity, and methodological simplicity. Abstract : Luminescent molecular probes and nanoscale materials have become important tools in biosensing and bioimaging applications because of their high sensitivity, fast response, specificity, and methodological simplicity. In recent years, there has been a notable advancement in fluorescent probes that respond to the subtle changes in subcellular microenvironments ( e.g., polarity, pH, and viscosity) or distribution of certain crucial biomarkers ( e.g., reactive oxygen species, ions, amino acids, and enzymes). The dynamic fluctuations of these bio-molecules in subcellular microenvironments control cellular homeostasis, immunity, signal conduction, and metabolism. Their abnormal expressions are linked to various biological disorders and disease states. Thus, the real-time monitoring of such bioactive species is intimately linked to clinical diagnostics. Appropriately designed luminescent probes are ideally suited for desired organelle specificity, as well as for reporting intracellular changes in biochemicals/microenvironmental factors with the luminescence ON response. In this perspective, we review our recent work on the development of fluorescent probes for sensing and imaging within sub-cellular organelles. We have also discussed the design aspects for developing a prodrug with a fluorescent probe as an integral part of possible theranostic applications. An overview of the design principles, photophysical properties, detection mechanisms, current challenges, and potential future directions of fluorescent probes is presented in this feature article. We have also discussed the limitations and challenges of developing the solution platform for sensing technologies in clinical diagnostics.